Supporting the Quality of Learning Objects Through Their Ranking Visualization - Morales Morgado, E. M.; Gómez Aguilar, D.A; García Peñalvo, F. J.; Therón Sánchez, R. (International Journal of Emerging Technologies in Learning (iJET), 2009)
The quality of Learning Objects (LOs) is currently being promoted by certain tools which consider specific criteria for their evaluation; however, there is no existing methodology that considers both the value assigned to the LO itself and the percentage related to the number of evaluators who have compared the quality of resources. As in the case of various products offered through the Internet backed by an assessment of users in a unified ranking, the purpose of this paper is to suggest a proposal for the automated assessments of experts who can clearly see the best or worst aspects in LO quality.